Language diversity in Indigenous Australia in the 21st century. Issue 1 (1st January 2019) - Simpson, Jane; Wigglesworth, Gillian
ABSTRACT: The diversity of language in Australia in pre-invasion times is well attested, with at least 300 distinct languages being spoken along with many dialects. At that time, many Indigenous people were multilingual, often speaking at least four languages. Today many of these languages have been lost, with fewer than 15 being learned by children as a first language. However, despite this, much diversity remains. This diversity includes the remaining traditional Indigenous languages (TILs) spoken in more remote areas, largely in the north of Australia, as well as the new varieties that have developed since the invasion, and the dialects of Aboriginal English spoken across Australia. In remote communities where TILs are spoken, individuals and in some cases communities often maintain a high level of multilingualism. However, diaspora populations of TIL speakers are emerging in cities such as Darwin, Katherine, Port Augusta and Kalgoorlie. In some communities, new varieties are emerging as speakers change the way they talk. These include 'new' mixed languages such as Light Warlpiri or Gurindji Kriol, as well as a wide variety of creoles, including, for example, Roper River Kriol, Fitzroy Valley Kriol and Yumplatok in the Torres Strait) and the various dialects of Aboriginal English spoken across the country. In this article, we explore this language diversity, examining its historical underpinnings and development, its implications for education and engagement in the wider community, and how Aboriginal people are using the new varieties to forge group identities.